Ketersediaan Kalium Tanah Vertisol untuk Meningkatkan Hasil Tanaman Padi Hitam Melalui Penambahan Cocopeat dan Sekam - Elly Istiana Maulida; Sartono Joko Santosa; Septi Kumala Sari (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Black rice is considered capable of increasing endurance because it contains the highest anthocyanin compounds compared to other rice. In fulfilling the demand for black rice in Sragen Regency there are still many obstacles, one of which is Vertisol soil. Vertisol soil has low available potassium which affects rice yields. To overcome this, cocopeat and rice husk were added to the growing medium. The purpose of this study, with the addition of cocopeat and rice husk to the growing medium, was able to increase the K-available Vertisol soil so that the yield of black rice increased. The research was carried out in March-August 2021 at the UPT Sragen Agriculture Service. Soil chemical analysis at the Laboratory of Chemistry and Soil Fertility FP UNS. This study has carried out using an RCBD with two factors, The first factor is a mixture of growing medium (M): M0: Control (soil), M1: Mixture of soil with cocopeat and M2: Mixture of soil with rice husk, and the second factor is black rice variety (V): V1: Cempo Ireng black rice, V2: Jlitheng black rice and V3: YR07 black rice. From the two factors, 9 treatment combinations were obtained and repeated 3x so that there were 27 polybags. Data were analyzed by the F test at a 5% level then followed by the DMR test at a 5% level. The results showed that the addition of cocopeat and rice husk to the growing medium was not able to increase the K-available Vertisol soil, but the addition of rice husk to the growing medium was able to increase the highest amount of filled grain compared to other treatments. Keywords: Planting media, Cempo Ireng rice, Jlitheng rice, YR07 rice, K-Available.